« Neue Kulturgeographie » - Débats et perspectives au sein de la nouvelle géographie culturelle germanophone - Mélina Germes; Georg Glasze; Florian Weber (Cybergeo, 2011)
Since the beginning of the 2000’s, a new school in German-speaking geography arose which is named “Neue Kulturgeographie” (new cultural geography). It is mainly inspired by the poststructuralism and by the English-speaking new cultural geography. On the basis of a constructivist approach, the signification of space and spatial forms is the main focus of the Neue Kulturgeographie’s researches. An important difference between these researches, however, lies on the very different social theories they are based on: action theory, system theory, discourse theory and critical approaches are the four main theories being used in the Neue Kulturgeographie. The aim of this paper is to introduce the French-speaking geographer to the Neue Kulturgeography and its debate. The reader will surely recognize the questions and problems shared by the social and cultural French- (and also English-) speaking geographies.